Gender inequality among champions and players’ reception of gender disproportion of utility support champions in league of legends - Doo Heon Song; Hae Kyung Rhee; Jeong Hoon Kim (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Designing female character in video game has been criticized as being sexually objectified and underrepresented in quantity (number of characters and their appearance rate in the game) and in quality (take only secondary role and inferior ability statistics given). In this paper, we analyze world leading multiple-user online battle arena game league of legends to see if previously criticized gender inequality of champions still stands and conduct a survey of 1,403 players of that game and asks how they feel about serious gender disproportion of utility support champions (all females). The result shows that league of legends still has serious gender disparity in performance parameters and there has been only a small change in 5-year span (2014-2019). The survey result tells us that game players also feel political incorrectness of such gender disproportion, but they accept such gender prototype because they have been taught as such as social role theory explains gender inequality issues.